2009
DOI: 10.1007/s12098-009-0120-3
|View full text |Cite
|
Sign up to set email alerts
|

Preputial adhesions — A misunderstood entity

Abstract: The majority of children referred with 'phimosis for circumcision' to this tertiary pediatric surgical centre were actually physiologic preputial adhesions that were managed with outpatient preputial adhesiolysis. This study underscores a lack of awareness amongst referring primary care physicians regarding preputial adhesions and the potential for an erroneous diagnosis of phimosis translating into unnecessary circumcisions in many young boys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…Their misdiagnosis leads to unnecessary anxiety in parents and over-referrals to urologists for circumcision. Of the cases referred to a urology clinic, it was found that only 8–14.4% of them had “true” phimosis needing surgical intervention [23, 24]. …”
Section: Defining Phimosismentioning
confidence: 99%
See 1 more Smart Citation
“…Their misdiagnosis leads to unnecessary anxiety in parents and over-referrals to urologists for circumcision. Of the cases referred to a urology clinic, it was found that only 8–14.4% of them had “true” phimosis needing surgical intervention [23, 24]. …”
Section: Defining Phimosismentioning
confidence: 99%
“…This nonsurgical adhesiolysis is found to be effective, cheap, and safe treatment for phimosis [23, 6264]. Eutectic mixture of local anaesthetics (EMLA) could be used prior to attempts at release of the preputial adhesions [65].…”
Section: Dilation and Stretchingmentioning
confidence: 99%
“…The separation of the prepuce/glans penis mucosa is usually complete by about 17 years of age. Studies have confirmed that preputial non-separation (adhesions) is very common in children and teenagers but resolves over time [3,6,7].…”
mentioning
confidence: 94%
“…Most of surgeons do not differentiate between physiological and pathological phimosis; and are being subjected to circumcision. 4 So circumcisions performed outnumber the conservative managed patients with phimosis. Due to anxiety the parents of these children may opt for circumcision.…”
Section: Introductionmentioning
confidence: 99%